CIRI DAN TIPE KATA BANTU BILANGAN DALAM BAHASA BALI - Ni Luh Komang Candrawati (Widyadari : Jurnal Pendidikan, 2020)
Generally, this paper is expected to contribute to the preservation and development of the Balinese language. In addition, it is also expected to continue efforts to standardize the Balinese language, as well as be able to contribute in the field of Balinese teaching. Specifically, this paper describes the characteristics and types of Balinese numeral classifier. The theory used in this study is a structural Linguistic theory, from some linguistic books and library materials that are relevant to the problem of this paper. Numeral classifier is a word or form that indicates the noun group, which follows the numeral itself (Kridalaksana, 1982: 76). According to Ramlan (1985: 54), numeral classifier is a word that lies behind the numeral to form a phrase called as a numeral phrase, which may be located in front of the nominal word. In principle, the numeral classifier is a word behind (follows) the number and shows the group of nouns or a number of phrases and may (can) be followed by the noun but positioned in front of the noun. That understanding is used in identifying Balinese numeral classifier. By this theory, it is found that Balinese numeral classifiers have structural and semantic characteristics. Its structural characteristics include morphological features and syntactic features. Morphological features are divided into two, namely the characteristics of a single form and the characteristics of complex form. The semantic characteristic is used to count the number of the noun (people, animals, or goods), for example the word 'ekor' to indicate the existence of an animal. By the type of Balinese numeral classifier, there are two types, namely endocentric type, that is in the form of attributive endocentric and exocentric type.